Assessment of Pharmacokinetic Effects of Herbal Medicines on Escitalopram - Jung YS; Jin BH; Choi JE; Park MS; Kim YW; Kang HW; Cho S; Kim CO (Dove Medical Press, 2024)
Yun Seob Jung,1 Byung Hak Jin,2 Ju Eun Choi,2 Min Soo Park,2 Young-Woo Kim,3 Hyung Won Kang,4 Sunyoung Cho,5 Choon Ok Kim2 1Department of Pharmacology, Yonsei University College of Medicine, Seoul, Korea; 2Department of Clinical Pharmacology, Severance Hospital, Yonsei University Health System, Seoul, Korea; 3School of Korean Medicine, Dongguk University, Gyeongju, Korea; 4College of Korean Medicine, Wonkwang University, Iksan, Korea; 5IntegroMediLab Co., Ltd, Seoul, KoreaCorrespondence: Choon Ok Kim, Department of Clinical Pharmacology, Severance Hospital, Yonsei University Health System, Seoul, Korea, Tel +82-2-2228-0455, Fax +82-2-2227-7890, Email delivery98@yuhs.acPurpose: Herbal medicines are occasionally used in combination with conventional antidepressants to mitigate various depression-associated symptoms. However, there is limited information on herb-antidepressant interactions. In this study, we investigated the pharmacokinetic (PK) effects of four herbal medicines (Gami-soyosan, Banhasasim-tang, Ojeok-san, and Bojungikgi-tang) on escitalopram, a commonly used antidepressant.Patients and Methods: In this open-label, fixed-sequence, three-period, crossover study, 18 participants were enrolled and divided into two groups. Each group received a 10 mg oral dose of escitalopram in period 1. Participants took escitalopram once daily and their assigned herbal medicines thrice a day for 7 d in periods 2 (group 1: Gami-soyosan, group 2: Ojeok-san) and 3 (group 1: Banhasasim-tang; group 2: Bojungikgi-tang). The primary endpoints were Cmax,ss and AUCtau,ss of escitalopram. Cmax,ss and AUCtau,ss in period 1 were obtained using nonparametric superposition from single-dose data. The PK endpoints were classified according to the CYP2C19 phenotype.Results: Of 18 participants, 16 completed the study. Systemic exposure to escitalopram resulted in a minor increase in the presence of each herbal medicine. The geometric mean ratios (GMRs, combination with herbal medicines/escitalopram monotherapy) and their 90% confidence intervals (CIs) for Cmax,ss and AUCtau,ss were as follows: Gamisoyosan- 1.1454 (0.9201, 1.4258) and 1.0749 (0.8084, 1.4291), Banhasasim-tang- 1.0470 (0.7779, 1.4092) and 1.0465 (0.7035, 1.5568), Ojeok-san- 1.1204 (0.8744, 1.4357) and 1.1267 (0.8466, 1.4996), and Bojungikgi-tang- 1.1264 (0.8594, 1.4762) and 1.1400 (0.8515, 1.5261), respectively. Furthermore, no significant differences in the GMRs of Cmax,ss and AUCtau,ss were observed across different CYP2C19 phenotypes in any of the groups.Conclusion: The co-administration of escitalopram with Gami-soyosan, Banhasasim-tang, Ojeok-san, or Bojungikgi-tang did not exert significant PK effects on escitalopram. These findings provide valuable insights into the safe use of herbal medicines along with escitalopram.Keywords: CYP2C19 phenotype, herb-drug interaction, antidepressant, geometric mean ratio